Gerakan Remaja Kreatif dalam Mengelola Sampah Di Desa Banaran Kecamatan ‎Tembarak Kabupaten Temanggung - Fika Khalwa Ngaisah; Ikhsan Salafudin (Universitas Teuku Umar, 2021)
Abstract The creative youth movement of Banaran Tembarak Temanggung Village is an activity that can be said to be normal, but in carrying it out it is not as easy as turning the palm of the hand because of problems arising from people's unconsciousness that they will process waste according to its type, as for several programs that have been realized with The good things in the village of Banaran Tembarak Temanggung are: (1) the stages of planning with social analysis, namely